Dengue beyond the tropics: a time-series study comprising 2015-2016 versus 2019-2020 at a children’s hospital in the City of Buenos Aires - Berberian, Griselda Virginia (2022)
Introduction: Dengue is a public health problem worldwide. It was originally confined to tropical and subtropical areas, but it is now present in other regions, such as Argentina. Epidemic outbreaks have been observed in the City of Buenos Aires since 2008, with few reports in children.Objective: To analyze and compare the clinical, epidemiological, laboratory, and evolutionary characteristics of the latest 2 dengue outbreaks outside the endemic area.Population and methods: Time-series study. Patients under 18 years of age with probable or confirmed dengue and evaluated in a children´s hospital of the City of Buenos Aires during the periods 2015-2016 and 2019-2020 were included.Results: A total of 239 patients were included; 29 (12%) had a history of travel. Their median age was 132 months (interquartile range: 102- 156). All had a fever. Other symptoms included headache in 170 (71%), myalgia in 129 (54%), and rash in 122 (51%). Forty patients (17%) had comorbidities. Warning signs were observed in 79 patients (33%); 14 (6%) developed severe dengue; 115 (45%) were hospitalized; none died. DENV-1 was the most common serotype. A history of travel and hospitalization prevailed in the first period; severe dengue and prior infection, in the second period.Conclusions: No patient died due to dengue in either study period. Statistically significant differences were observed in the frequency of hospitalization; a history of travel was more common in the 2015-2016 period and severe dengue, in the 2019-2020 period.